2016
DOI: 10.3389/fpls.2015.01202
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Patterns of Four Tropical Bamboo Species Assessed with Sap Flux Measurements

Abstract: Bamboos are grasses (Poaceae) that are widespread in tropical and subtropical regions. We aimed at exploring water use patterns of four tropical bamboo species (Bambusa vulgaris, Dendrocalamus asper, Gigantochloa atroviolacea, and G. apus) with sap flux measurement techniques. Our approach included three experimental steps: (1) a pot experiment with a comparison of thermal dissipation probes (TDPs), the stem heat balance (SHB) method and gravimetric readings using potted B. vulgaris culms, (2) an in situ calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 48 publications
2
34
0
1
Order By: Relevance
“…In most studies, the number of plants directly analysed for water use is lower than the number of plants in the stand. In addition, recently increasingly monocot species such as bamboos and palms came into the focus of transpiration studies (Mei et al, 2016;Röll et al, 2015), in which intraspecific diameter variation may be low but nonetheless variation in water use occurs. Scaling is thus a critical issue that needs to be optimized in order to improve transpiration estimates and to reduce associated uncertainties (Hatton & Wu, 1995;Jarvis, 1995 Candidate variables for scaling include tree diameter, crown metrics, and leaf area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, the number of plants directly analysed for water use is lower than the number of plants in the stand. In addition, recently increasingly monocot species such as bamboos and palms came into the focus of transpiration studies (Mei et al, 2016;Röll et al, 2015), in which intraspecific diameter variation may be low but nonetheless variation in water use occurs. Scaling is thus a critical issue that needs to be optimized in order to improve transpiration estimates and to reduce associated uncertainties (Hatton & Wu, 1995;Jarvis, 1995 Candidate variables for scaling include tree diameter, crown metrics, and leaf area.…”
Section: Introductionmentioning
confidence: 99%
“…Stem diameter has some limitations that include a potentially slow response to concurrent dynamics in the stand such as crown damages or crown expansions into gaps. In addition, recently increasingly monocot species such as bamboos and palms came into the focus of transpiration studies (Mei et al, 2016;Röll et al, 2015), in which intraspecific diameter variation may be low but nonetheless variation in water use occurs.…”
Section: Introductionmentioning
confidence: 99%
“…With increases in VPD, trees undergo severe water stress and stomatal conductance decreases to prevent excessive water loss, thereby leading to weakening of transpiration and MDS decreases. This process has been observed in some study systems [44,46] but not in many others [24,47,48] that instead observed linear and positive increases of MDS with VPD. These differences primarily depend on the level of plant water stress that is experienced [49], wherein the positive relationships between MDS and VPD were almost always observed under non-limiting soil water availability.…”
Section: Environmental Factors That Influence Daily Stem Variation Dumentioning
confidence: 69%
“…Esta condición podría por lo tanto ser reflejada en menor contenido de humedad en los culmos de este sitio. La relación entre la disponibilidad de agua en el suelo y su efecto en los árboles ha sido descrita por Borchert (1994) y, de acuerdo con Mei et al (2015), quienes evaluaron los patrones de uso de agua en cuatro especies de bambú, estas plantas resultan más susceptibles que los árboles a los cambios de humedad en el suelo. Aquí también se encontró una relación entre menores diámetros y mayor flujo de savia a través de los mismos, lo que implica seguramente más haces vasculares para el transporte de la misma.…”
Section: Discussionunclassified